Kurikulum 2013 dalam pengimplementasian Pembelajaran PAI di Sekolah Yayasan Perguruan IRA - Batubara, Siti Rahmi; Hidayah, Nurul Habibatul; Candra, Azman; Neliwati, Neliwati (MODELING: Jurnal Program Studi PGMI, 2023)
In principle, the implementation of the 2013 curriculum is needed by teachers in schools as a preparation of Learning Implementation Plans (RPP), this is expected to provide a balance between cognitive, affective and psychomotor aspects in a balanced manner. In this study using a qualitative descriptive method. Research in descriptive form is research that seeks to describe an event, symptoms and events that are happening now. To obtain data that is suitable for research purposes, the techniques used in collecting data in this study are observation techniques, interview techniques and documentation techniques. In the 2013 curriculum there is also an educational development strategy, one of which is the addition of lesson hours. The learning model implemented in the 2013 curriculum at the IRA Education Foundation is a problem-based learning model, a project-based learning model and a learning model through discovery or discovery. The advantages of implementing PAI learning are that students understand more about PAI learning in the 2013 curriculum. Weaknesses in the implementation of PAI learning in the 2013 curriculum are that it takes a lot of time for students to learn a subject.